Effect of a 10000m kayak sprint on redox status, muscle damage and inflammation markers in elite male kayakers - Teixeira, V. H.; Valente, H.; Casal, S.; Marques, F.; Moreira, P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Sprint kayaking is a demanding exercise that can generate reactive oxygen species (ROS) to a level that surpasses body`s antioxidant capacity causing oxidative stress and damage. This study aimed to determine the response of plasmatic antioxidants and markers of lipid peroxidation, muscle damage, inflammation and physiological stress to a 1000m flatwater kayaking simulated race in elite kayakers. Methods: Superoxide dismutase (SOD), glutathione reductase (Gr), glutathione peroxidase (GPx) and creatine kinase (CK) activities and levels of uric acid, alpha-tocopherol, alpha-carotene, beta-carotene, lycopene, lutein + zeaxanthin, total antioxidant status (TAS), thiobarbituric acid reactive substances (TBARS), interleukin-6 (IL-6), cortisol, lipoproteins and hematologic parameters were determined in 15 male kayakers before and 15min after the kayak bout. Post-exercise measurements were corrected for hemoconcentration. Results: Both enzymatic and non-enzymatic antioxidants were unaffected by exercise, with the exception of alpha-carotene which decrease (0.22 to 0.18 mmol/L; P = 0.013). The exercise bout caused a decline in TAS (1.46 to 1.13 mmol/L; P = 0.001) and an augment in CK (256 to 304 IU/L; P = 0.023), uric acid (5.0 to 5.4 mg/dL; P = 0.016), TBARS (5.4 to 9.0 mmol/L; P < 0.001) and IL-6 (1.8 to 2.4 pg/mL; P = 0.028). Post-exercise TBARS and TAS were inversely correlated (r= -0.569, P = 0.027). Cortisol levels were not altered by kayaking (188 and 193 nmol/L; P = 0.824). Discussion: The stability of alpha-tocopherol after kayaking suggests that it was not consumed or mobilized from adipose tissues, which is consistent with the maintenance of triglycerides levels. Also, the lack of change in carotenoids agrees with the maintenance of their main carrier (LDL). The increased post-exercise uric acid likely resulted from the enhancement of purine metabolism or the inhibition of its renal clearance by lactate. Therefore, the observed decrement in TAS after the kayak bout may reflect a compromised status of other aqueous antioxidants, such as ascorbic acid (not measured). This lowering in antioxidant status was associated with an increase in lipid peroxidation following exercise. The augmented post-exercise TBARS reflect the efflux of peroxides from muscles into plasma. ROS attack of polyunsaturated fatty acids increases the permeability of cell membranes causing the efflux of miocellular CK. However, no correlation between TBARS and CK was detected. The modest rise in CK may be explained by the concentric nature of kayaking and the familiarization with the exercise by athletes. The slight augment in IL-6 after exercise may be due to the type (concentric) and duration (234.0 ± 5.8 sec) of the exercise or to the subjects` training status. Our data indicate that a single 1000m kayak bout impair antioxidant status and induce lipid peroxidation, muscle damage and inflammation even in high-level kayakers.